Estimativa da divergência entre ecótipos de braquiária baseada em descritores quantitativos e qualitativos - Torres, Francisco Eduardo; Valle, Cacilda Borges do; Lempp, Beatriz; Teodoro, Paulo Eduardo; Rigon, João Paulo Gonsiorkiewicz [UNESP]; Ribeiro, Larissa Pereira; Corrêa, Caio Cézar Guedes; Júnior, Roque Apolinário Alves da Luz (Universidade Federal de Santa Maria, 2015)
This study aimed to estimate the genetic divergence between Urochloa brizantha ecotypes based on quantitative, qualitative descriptors and their joint analysis to select the promising to release as cultivars of this species. Eight ecotypes (B1, B2, B3, B4, B5, B6, B8) and cultivar 'Marandu' of U. brizantha were implanted into pickets with 1000m2 each, with two repetitions. Five quantitative descriptors were evaluated [leaf area (ALF), length and width of leaf blades (CLF and LLF, respectively), dry mass (MS), mass of dry matter (MMS) and proportion of leaf blade in MS (PLF)] in two forage samples, being a representative of rainfall, in February 2000, and another in the dry period, in August 2000. It was measured the qualitative descriptors: shear strength (RC), volume of accumulated gas in fast and slow fraction (A and B, respectively), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF ), cellulose (CEL), lignin in sulfuric acid (LIG), silica (SIL) and in vitro digestibility of organic matter (IVOMD). There was considerable genetic divergence in U. brizantha ecotypes, especially regarding to quantitative descriptors. Based on the groupings of quantitative, qualitative descriptors and their joint analysis, the grouping containing of B1, B3 and B5 with 'Marandu' can result in promising U. brizantha ecotypes

O presente trabalho objetivou estimar a divergência genética entre ecótipos de Urochloa brizantha com base na análise de descritores quantitativos, qualitativos e sua análise conjunta a fim de selecionar os promissores para liberação como cultivares desta espécie. Oito ecótipos (B1, B2, B3, B4, B5, B6, B8) e a cultivar 'Marandu' de U. brizantha foram implantados em piquetes, com 1000m2 cada, em duas repetições. Foram avaliados cinco descritores quantitativos e dez qualitativos no período seco e das águas. Os descritores quantitativos foram: área foliar, comprimento e largura das lâminas foliares, massa seca (MS) e proporção de lâmina foliar na MS. Os descritores qualitativos mensurados foram: resistência ao cisalhamento, volume de gás acumulado na fração rápida e lenta, proteína bruta, fibra em detergente neutro, fibra em detergente ácido, celulose, lignina em ácido sulfúrico, sílica e digestibilidade in vitro da matéria orgânica. Houve divergência genética entre os ecótipos de U. brizantha, especialmente em relação aos descritores quantitativos. Com base nos agrupamentos dos descritores quantitativos, qualitativos e sua análise conjunta, o agrupamento contendo de B1, B3 e B5 com 'Marandu' podem resultar em ecótipos promissores de U. brizantha
Estimation of genetic divergence between braquiária ecotypes based on quantitative and qualitative descriptors
Keywords: Joint analysis; Marandu; Qualitative descriptors; Quantitative descriptors; Análise conjunta; Cultivar Marandu; Descritores qualitativos; Descritores quantitativos